Tashîf dan Tahrîf: Telaah atas Kesalahan Teks dalam Tradisi Islam - Rizamul Malik Akbar; Masruri, M. Hadi; Al Kholidy, Muhammad Firdaus; Zakiyah, Nailiatuz; Roziqin, Zainur (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This article examines the phenomena of taṣḥīf and taḥrīf as forms of textual error in the Islamic scholarly tradition and their implications for both classical and modern philological practices. This study is significant as it reveals how variations in diacritical marks, letter forms, and semantic deviations can influence the understanding and authenticity of transmitted texts. The research aims to elaborate on the definitions, causes, and positions of taṣḥīf and taḥrīf within the framework of classical Arabic textual criticism. The study employs a qualitative approach through library research, drawing primarily from Taḥqīqu an-Nuṣūṣ wa Nashruhā by ‘Abd as-Salām Muḥammad Hārūn. The findings indicate that: (1) taṣḥīf is technical in nature, while taḥrīf involves semantic alteration; (2) their causes include technical, linguistic, and cultural factors; and (3) the treatment of taṣḥīf and taḥrīf in philology is carried out through methodological solutions such as tarjīḥ al-riwāyāt (weighing and preferring textual variants) and taṣḥīḥ al-akhṭā’ (correction of textual errors) as integral components of the practice of taḥqīq al-nuṣūṣ (critical editing of texts). This study affirms philology’s role as a discipline dedicated to preserving the integrity of texts and the intellectuall heritage of Islamic civilitazion.